CONSUMER SOCIETY AND PERSUASIVE DISCOURSE: A LINGUISTIC ANALYSIS OF CONTEMPORARY ADVERTISEMENTS - Dela-Savia Braga e Castro, Laura; do Nascimento Portela, Daniele (Revista Gênero e Interdisciplinaridade, 2022)
The purpose of this paper is to analyze language choice in advertising discourse and how individuals are affected by persuasion. In order to examine a society supported by consumption, Aristotle’s (1979) concepts of rhetoric will be central to this work. Observing how lexical resources are used in order to compose the persuasive discourse, we will use the writings of Roman Jakobson (1991). As an analytical procedure, we will turn our attention to five contemporary advertisements in the media, such as newspapers, television and Internet, highlighting how the advertising language becomes essential to induce the receiver to consumption. At the same time that consumerist practices are inserted in a cycle, individuals are led to make certain decisions and thus constitute themselves as agents in the process of social construction, going beyond the acquisition of only one good or service.